Successful Repair of Acute Type A Aortic Dissection 15 Years Following Bilateral Lung Transplantation. Issue 1 (19th November 2015) - Hermsen, Joshua L.; Madathil, Ronson; Berfield, Kathleen S.; Li, Kevin; Smith, Jason W.; Mulligan, Michael S.
Abstract: This report describes a patient treated for acute type A aortic dissection 15 years after undergoing bilateral lung transplantation by a clamshell thoracotomy. doi: 10.1111/jocs.12671 (J Card Surg 2016;31:72–73)